TO STUDY THE ULCEROPROTECTIVE EFFECT OF LEAVES OF MORINGA OLEIFERA ON EXPERIMENTALLY INDUCED INFLAMMATORY BOWEL DISEASE ON ANIMAL MODELS - SHIPRA KAUSHIK; SHOBHIT KAUSHIK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was carried out to evaluate the ulceroprotective effect of ethanolic extract of leaves of Moringa oleifera (EEMO) on experimentally induced inflammatory bowel disease (IBD) on Albino (Wistar strain) rats. Methods: The rats were divided into four groups of six animals each. Group A and Group B received gum acacia per orally (P.O.), Group C received EEMO in dose of 500 mg/kg/day P.O., and Group D received 5-aminosalicylic acid (5-ASA) in the dose of 100 mg/kg/day P.O. All the animals were pre-treated with respective drugs (volume of drugs was kept constant at 10 ml/kg) for 5 days, along with the normal diet. On 5th day, animals were kept fasting for 12 h (overnight), and IBD was induced next morning in Groups B, C, and D by the administration of 1 ml of 4% acetic acid solution transrectally (TR). Group A (normal control) received 0.9% normal saline TR instead. Results: The results have been shown that EEMO has significant activity against experimentally induced IBD when compared to the experimental control, with near normalization of colon architecture both macroscopically as well as microscopically. Tissue oxidative stress was reduced with significant improvement in tissue levels of superoxide dismutase (SOD) and catalase (CAT). Furthermore, significant improvement in levels of myeloperoxidase (MPO) was observed. Conclusion: It is concluded that EEMO has got potent activity against experimentally induced IBD due to its anti-inflammatory and antioxidant properties.